2022
DOI: 10.1002/smll.202106515
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure Optimized BiFeO3‐SrTiO3 Lead‐Free Ceramics with Ultrahigh Energy Storage Performance

Abstract: capacitors), dielectric capacitors are promising candidates for advanced pulsed power applications owing to their high power density and fast charge/discharge speed. [6][7][8] Ceramic dielectrics show excellent temperature stability and mechanical robustness, are promising materials for use in extreme conditions. [9] Anti-ferroelectric ceramics (such as PbTiO 3 -and Pb(Zr,Ti)O 3 -based dielectrics) display double polarization-electric field (P-E) loops, which have tremendous potential for realizing high energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 60 publications
7
93
0
Order By: Relevance
“…BF-ST is being studied for energy storage application. Recently, Yan et al reported the ultrahigh energy density of 9.3 J/cm 3 and excellent efficient with 90% as shown in Figure 5a,b, which is an excellent energy density property compared to the that of other lead-free system, as shown in Figure 5c [65]. Energy storage performance dependent (a) frequency, (b) temperature for 0.35BiFeO 3 -0.65SrTiO 3 ceramics.…”
Section: Lead-free Piezoelectricsmentioning
confidence: 88%
See 3 more Smart Citations
“…BF-ST is being studied for energy storage application. Recently, Yan et al reported the ultrahigh energy density of 9.3 J/cm 3 and excellent efficient with 90% as shown in Figure 5a,b, which is an excellent energy density property compared to the that of other lead-free system, as shown in Figure 5c [65]. Energy storage performance dependent (a) frequency, (b) temperature for 0.35BiFeO 3 -0.65SrTiO 3 ceramics.…”
Section: Lead-free Piezoelectricsmentioning
confidence: 88%
“…BF-ST is being studied for energy storage application. Recently, Yan et al reported the ultrahigh energy density of 9.3 J/cm 3 and excellent efficient with 90% as shown in Figure 5a,b, which is an excellent energy density property compared to the that of other lead-free system, as shown in Figure 5c [65]. In view of these technological breakthroughs and constraints in lead-free piezoelectric solid solution systems, BF-based systems have been studied to reveal its potential to be used in applications requiring particularly high temperature and stable piezoelectric response.…”
Section: Lead-free Piezoelectricsmentioning
confidence: 91%
See 2 more Smart Citations
“…[2][3][4] At present, for dielectric materials, it can mainly be divided into three categories: ceramics, polymer composites, and glassceramics. 5 Many research studies have focused on ceramics, but the applied electric field for ceramics is gener-ally lower than 400 kV/cm, [6][7][8][9][10][11] which limits the rise of energy storage and power density. Moreover, for polymer composites, the low permittivity and poor thermal stability also limit their wide applications.…”
Section: Introductionmentioning
confidence: 99%